Analisis Peran Model Matematika Dalam Perencanaan Drainase Perkotaan Sebagai Upaya Mitigasi Banjir Di Era Perubahan Iklim - Mendrofa, Elrica Fajariang (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Climate change has led to an increase in rainfall intensity and uncertainty, which has significantly contributed to the rising occurrence of urban flooding. One of the main causes of flooding in urban areas is the inadequacy of drainage systems that were designed based on outdated hydrological data. In urban drainage planning, mathematical models play an important role in analyzing rainfall characteristics, estimating runoff discharge, and determining appropriate drainage channel capacity. This study aims to analyze the role of mathematical models in urban drainage planning as an effort to mitigate flood risks in the era of climate change. The methods used include rainfall data analysis, determination of design rainfall intensity, runoff discharge calculation using the Rational Method, and evaluation of drainage channel capacity based on open channel flow principles. The results indicate that the application of appropriate mathematical models can improve the accuracy of drainage system planning and reduce the potential for surface water inundation. Therefore, the systematic use of mathematical models is essential to develop more adaptive and sustainable urban drainage systems.